Etika dan Regulasi Dalam Komunikasi Politik (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
This study discusses ethics in political communication in Indonesia with a focus on regulations, digital media, and the rise of hoaxes during the election. The study is directed at elements of political communication such as communicators, messages, media, communicants, effects, and information interference. The study also reviews communication models (actions, interactions, transactions) and regulations such as the KIP Law, the ITE Law, and Presidential Regulation No. 82 of 2024. The main objective is to understand the application of ethics and the effectiveness of regulations in countering political hoaxes. The method used is descriptive qualitative through literature studies, legal documentation, and media analysis. The results show that political communication ethics are still weak due to the lack of regulatory enforcement and low digital literacy in society.